Pengaruh Electronic Word Of Mouth Melalui Instagram Terhadap Keputusan Pembelian Pada Kafe Di Kota Pekanbaru - Amie Dhiza; Zulkarnain; Any Widiyatsari (Jurnal Economica, 2020)
The purpose of this study is to examine and analyze the effect of intensity on purchasing decisions. To analyze the effect of content on purchasing decisions. To analyze the effect of positive valency on purchasing decisions. To analyze the effect of negative valency on purchasing decisions. The population in this study are visitors of the cafes that are the object of research in the city of Pekanbaru, especially for cafes that are not on the pratocol road. The sample in this study were 110 people. The sample method uses the area sampling method. The data used in this study are primary and secondary data, while data collection techniques are using questionnaires. The data analysis technique used in this study is multiple linear regression. Research findings indicate that intensity has a positive and significant effect on purchasing decisions. Content has a positive and significant effect on purchasing decisions. Valency positive has a positive and significant effect on purchasing decisions. This means that more and more positive comments from consumers on the service and food and drinks served at a cafe, will increase consumer purchasing decisions at the cafe even to people who have never been to the cafe. Valency negative and significant negative effect on purchasing decisions. This means that the more negative comments or complaints of consumers over services and food and drinks served at a cafe, the consumer's purchasing decisions at the cafe will decrease.